2017
DOI: 10.1088/1361-665x/aa8497
|View full text |Cite
|
Sign up to set email alerts
|

Application of encapsulated superabsorbent polymers in cementitious materials for stimulated autogenous healing

Abstract: Superabsorbent polymers have shown potential for use in mortar and concrete as self-healing agents. The main drawback is, however, that these superabsorbent polymers also absorb mixing water during the preparation and casting of mortar or concrete, leading to a loss in workability. To avoid the absorption of mixing water, superabsorbent polymers were coated using a fluid bed spraying process. The barrier coating consisted of three successive coating layers: polyvinylbutyral as primer/wetting layer, cyclo-olefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
(54 reference statements)
5
31
0
2
Order By: Relevance
“…The water absorption capacity of these SAPs in DW and CS followed a similar trend as the maximum amount of water absorbed was higher in the case of DW than in the case of CS for all SAPs, a behavior which is in accordance with literature . Consequently, it is concluded that when SAPs are incorporated in cement as admixtures it is preferable for them to be directly added in cement pastes where the values of iconicity and pH are high, thus suppressing their initial swelling during mixing, as also found in literature . Nevertheless, significant differences were observed among the different SAPs .…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The water absorption capacity of these SAPs in DW and CS followed a similar trend as the maximum amount of water absorbed was higher in the case of DW than in the case of CS for all SAPs, a behavior which is in accordance with literature . Consequently, it is concluded that when SAPs are incorporated in cement as admixtures it is preferable for them to be directly added in cement pastes where the values of iconicity and pH are high, thus suppressing their initial swelling during mixing, as also found in literature . Nevertheless, significant differences were observed among the different SAPs .…”
Section: Resultssupporting
confidence: 88%
“…This fact can be assigned to both the rigidity of the inorganic shell and to its uniform and solid formation. Should there have been defects in the inorganic shell, in means of cracks, it is believed that the organic core would have swollen fully outside the inorganic shell, causing the structure deterioration of the SAP particles as reported in literature . Τhe EDS analysis confirms the successful encapsulation of the polymeric core into the inorganic shell due to the presence of silicon and calcium elements in the SAPs of P(MAANa‐co‐EGDMA)@SiO 2 (Si content 6.88 wt%) and P(MAANa‐co‐EGDMA)@CaO‐SiO 2 (Si content 14.33 wt.% and Ca content 13.70 wt.%), respectively.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations